Is the negative evaluation of dental services among the Brazilian elderly population associated with the type of service? - Andréa Maria Eleutério de Barros Lima Martins; Lorena Amaral Jardim; João Gabriel Silva Souza; Carlos Alberto Quintão Rodrigues; Raquel Conceição Ferreira; Isabela Almeida Pordeus (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
This study aimed at identifying the prevalence of the negative evaluation of dental services among elderly Brazilians and at investigating whether the prevalence was higher among those using public or philanthropic provider services than among those paying privately or using private health plans. Additionally, factors associated with this negative assessment were identified. Interview and survey data were collected in the residences of participants by trained and calibrated examiners as part of a national epidemiological survey of oral health conditions of the Brazilian population in 2002/2003. The dependent variable was obtained in response to questions regarding whether the participant had ever used dental services, the frequency of use, and the quality of this service. Potential responses to the questions regarding the quality of service were very poor or poor, fair, and good or very good. The main independent variable was the system of health care used with potential responses being health plan or private, public, and philanthropic services. We conducted univariate (linear tendency χ2test) and multiple descriptive analyses, and the partial proportional Odds model for ordinal logistic regression. Among the elderly, 196 (3.7%) evaluated the provided services negatively (very poor or poor). Participants with the following responses were more likely to evaluate the services negatively: those who had used public or philanthropic services, men, those with higher education, the ones who had not received information about preventing dental problems, those who perceived pain in their teeth and gums in the last six months, and those who self-reported their oral health and speech was poor. In conclusion, elderly Brazilian users of public and philanthropic services were more likely than users of private or insurance-based plans to evaluate their dental services negatively, regardless of the other investigated variables.